Spiritualitas anak Perspektif Pendidikan Islam (Analisis Konseptual kecerdasan spiritual sejak usia dini) - M. Shofwan Hadi; Ummidlatus Salamah; Dwi Dian Wigati; Siti Nurjanah (Alzam: Journal of Islamic Early Childhood Education, 2025)
Spiritual intelligence serves as the fundamental foundation for character formation in children from an early age, particularly within the framework of Islamic education. This study employs a qualitative approach using library research to explore the conceptual understanding of children's spiritual intelligence. This method enables an in-depth analysis of both classical and contemporary literature from Islamic sources as well as theories of developmental psychology and modern spiritual intelligence. The analysis follows systematic and iterative stages of data reduction, data presentation, and conclusion drawing to achieve a comprehensive understanding. Research on children's spirituality from the perspective of Islamic education reveals that spiritual intelligence is an innate spiritual potential present from birth, which can be nurtured through guidance, habituation, and a supportive environment. Islamic education emphasizes the integration of spiritual values into children's education through three main approaches: philosophical (morality, compassion), psychological (integration of Islamic values with modern psychology), and prophetic pedagogy (the exemplary model of Prophet Muhammad PBUH). The development strategies are holistic, including the habituation of worship practices, curriculum integration, teacher role modeling, family involvement, and the use of technology. Its implications for educational practice include the habituation of religious values, use of visual media such as illustrated stories, the central role of parents, and direct experiences such as fasting, all aimed at establishing a strong spiritual foundation from an early age